(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2021)
The ratification of the European Social Charter (revised) and of the Additional Protocol providing a system of collective claims represent another step in the process of internationalization of social rights. The European Committee of Social Rights in the Council of Europe issues “decisions”, the insertion of which in the internal legal system is not easy. It is appropriate to carry out both a legal and budgetary analysis of the system.